A Characterization of the Diffuse Galactic Emissions in the Anticenter of the Galaxy. (29th January 2013) - Fauvet, L.; Macías-Pérez, J. F.; Hildebrandt, S. R.; Désert, F.-X.
Abstract : Using the Archeops and WMAP data, we perform a study of the anticenter Galactic diffuse emissions—thermal dust, synchrotron, free-free, and anomalous emissions—at degree scales. The high-frequency data are used to infer the thermal dust electromagnetic spectrum and spatial distribution allowing us to precisely subtract this component at lower frequencies. After subtraction of the thermal dust component, a mixture of standard synchrotron and free-free emissions does not account for the residuals at these low frequencies. Including the all-sky 408 MHz Haslam data we find evidence for anomalous emission with a spectral index of −2.5 in T R J units. However, we are not able to provide coclusion regarding the nature of this anomalous emission in this region. For this purpose, data between 408 MHz and 20 GHz covering the same sky region are needed.